PENYULUHAN PROTOKOL CARING TERHADAP MAHASISWA KEPERAWATAN TINGKAT PERTAMA - Andria Pragholapati; Edy Suprayitno; Eni Hidayati; Suhartini Ismail (Universitas Negeri Medan, 2023)
Nursing students need to have a sense of being cared to maintain their own ability to care for others. The objectives of this community service are 1. To increase knowledge about the concept of Caring throughout the Life Span, and 2. To increase students' understanding of how caring behavior is in the process and practice of nursing, and as a means of student learning. The method used in this community service activity is Health Education and Training regarding Caring Protocols. The educational effect of caring protocols among first-degree nursing students revealed that, along with faculty, nursing students can also become role models for Caring.Â